Evaluation of “Helicobacter heilmannii” Subtypes in the Gastric Mucosas of Cats and Dogs - Priestnall, Simon L. (American Society for Microbiology, 2004)
Infection with candidatus “Helicobacter heilmannii” is associated with gastritis and mucosa-associated lymphoid tissue lymphoma in people. Infection with “H. heilmannii” type 1 predominates (80%) and is thought to be acquired from dogs, cats, or pigs. We further examined the zoonotic potential of dogs and cats by amplifying gastric DNA from cats (n = 45) and dogs (n = 10) with primers against “H. heilmannii” ureB and 16S rRNA genes and sequencing the products. Fluorescence in situ hybridization (FISH) with eubacterial and “H. heilmannii”-specific probes was employed to directly visualize “H. heilmannii” types and their intragastric distribution. ureB sequences of “H. heilmannii” amplicons clustered with human and feline isolates of “H. heilmannii” and were distinct from the “H. heilmannii”-like organisms (HHLO) H. felis, H. salomonis, and H. bizzozeronii. 16S ribosomal DNA sequences in 20 “H. heilmannii”-infected cats and dogs were distinct from “H. heilmannii” type 1 and “H. suis” and clustered with “H. heilmannii” types 2 and 4. FISH confirmed the presence of “H. heilmannii” types 2 and 4 in dogs but failed to definitively characterize the “H. heilmannii” types present in cats. In infected dogs, “H. heilmannii” inhabited the gastric mucus and glands, and in dogs coinfected with other HHLO it shared the same gastric niche. The results indicate that dogs and cats are predominantly colonized by “H. heilmannii” bacteria that are distinct from type 1 and from “H. suis.” As “H. heilmannii” type 1 predominates in people, the zoonotic risk posed by dogs and cats is likely small.